2022
DOI: 10.3934/math.2022297
|View full text |Cite
|
Sign up to set email alerts
|

Refinements of Jensen's inequality and applications

Abstract: <abstract><p>The principal aim of this research work is to establish refinements of the integral Jensen's inequality. For the intended refinements, we mainly use the notion of convexity and the concept of majorization. We derive some inequalities for power and quasi–arithmetic means while utilizing the main results. Moreover, we acquire several refinements of Hölder inequality and also an improvement of Hermite–Hadamard inequality as consequences of obtained results. Furthermore, we secure several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Jensen's inequality has a very strong relationship with ordinary convexity in the sense that it generalizes the definition of convex function. Another important fact about this inequality is that it is the origin of many other classical inequalities [23].…”
Section: Introductionmentioning
confidence: 99%
“…Jensen's inequality has a very strong relationship with ordinary convexity in the sense that it generalizes the definition of convex function. Another important fact about this inequality is that it is the origin of many other classical inequalities [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they compared their main results with some other earlier established improvements of Jensen's inequality and showed that the obtained improvements provided better estimations for the Jensen difference. Saeed et al [60] provided refinements of the celebrated integral Jensen inequality via the theory of majorization. With the help of these, refinements of the Hölder and Hermite-Hadamard inequalities were provided.…”
Section: Remarkmentioning
confidence: 99%
“…Furthermore, they also granted applications of the improved Jensen inequality in information theory. Saeed et al 36 established some refinements of the Jensen inequality by the support of majorization results. They discussed some consequences of their refinements for means, Hölder and Hermite‐Hadamard inequalities and also presented application for divergences and Shannon entropy.…”
Section: Introductionmentioning
confidence: 97%